Manajemen Dakwah Ustad Sarung - Sarja Sarja; Ahmad Faqih Udin (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
The purpose of this study is to determine the management used by ustad sarang in da'wah in tanjungsari village, so that da'wah can continue to exist in the community. The method used in this study is a descriptive method using qualitative data, to reveal that ustad sarung Tanjungsari Wanasar village, Brebes Regency preaches using management, for data collection. The author uses data collection tools with interviews, observations and documentation, while the analysis uses descriptive qualitative methods. The results of this study showed that Ustad Sarung was an Ustad who graduated from Salafiyah (traditional) pesantren. and use management so that da'wah activities can run well in terms of time and place of recitation so that the community as pilgrims are able to carry out recitation activities without obstacles, because Ustad Sarung himself has many activities both da'wah and as community leaders, starting from the daily routine of da'wah, which is weekly, and monthly, not to mention events outside the schedule that are sometimes sudden. With da'wah management which includes planning, organizing, mobilizing, and evaluating, the recitation at the home of the mothers of Tanjungsari Village, Wanasari District, Brebes Regency can run as expected.